1995
DOI: 10.1007/s002030050248
|View full text |Cite
|
Sign up to set email alerts
|

Buoyant density of Escherichia coli is determined solely by the osmolarity of the culture medium

Abstract: In previous studies, we had shown that the buoyant density of Escherichia coli is determined by the osmolarity of the growth medium by varying the osmolarity of the medium with NaCl or sucrose. However, the buoyant density of the cells always exceeded that of the growth medium. Here we determined the effect of medium with a buoyant density greater than the expected buoyant density of cells by adding Nycodenz to Luria broth. Percoll gradients of cells were analyzed by laser light scattering. The buoyant density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…To modify the density of YEPD (yeast extract/peptone supplemented with 2% glucose) we selected Percoll (Sigma-Aldrich), a colloidal silica suspension, for its low osmolality, low viscosity, and general impermeability of biological membranes (17). Experiments with Histodenz (Sigma-Aldrich) showed density changes for arrested yeast, likely through an osmotic response, such as is observed in bacteria (18). The resolution of the 8-μm-tall SMR used for these experiments is ∼3 fg (1-Hz bandwidth).…”
Section: Resultsmentioning
confidence: 96%
“…To modify the density of YEPD (yeast extract/peptone supplemented with 2% glucose) we selected Percoll (Sigma-Aldrich), a colloidal silica suspension, for its low osmolality, low viscosity, and general impermeability of biological membranes (17). Experiments with Histodenz (Sigma-Aldrich) showed density changes for arrested yeast, likely through an osmotic response, such as is observed in bacteria (18). The resolution of the 8-μm-tall SMR used for these experiments is ∼3 fg (1-Hz bandwidth).…”
Section: Resultsmentioning
confidence: 96%
“…Though this technique does not allow accurate quantifications, it is used here for a rough estimation that showed that PCD is a highly abundant protein that makes between 5 and 10% of the total soluble protein. The following assumptions were taken into account to estimate the cellular PCD concentration in ‘ A. aromaticum ’: (i) density of a standard Gram‐negative cell is 1.1 g ml −1 (Baldwin et al ., ), (ii) dry mass of cells is 30% of wet mass, (iii) protein accounts for ≈ 50% of dry mass, (iv) soluble protein is ≈80% of total protein and (v) PCD makes 7.5% of soluble protein. Using these numbers 1 mg of cells (wet mass) contained approximately 9 mg PCD.…”
Section: Resultsmentioning
confidence: 99%
“…These factors include differences in bacterial species (36), bacterial strains (22,30), type of intracytoplasmic membranes in methanotrophic bacteria (33), composition (22) and osmolarity (2,3,4) of the growth medium, hyperosmotic shock (5), mutation causing overproduction of proline (1), antibiotic (␤-lactam) resistance mutation (8), presence of capsule (28), growth rate (38), degradation of DNA and RNA (30), cell size (31), and the phase of the cell division cycle (11). Further elaborate biochemical work will be required to clarify which factors are involved in the change of buoyant density under the present experimental conditions.…”
Section: Discussionmentioning
confidence: 99%